Automatic Irrigation System - Nandhakumar T; Vidhya S; Jenita Shiny S (Journal of Electronic Design Engineering, 2017)
Agriculture is the backbone of Indian Economy. Irrigation is a basic determinant factor of Agriculture and it is the most powerful constrains on the increase of agricultural production. Irrigation is affected by highly inadequate quantity and quality of water, soil and minerals which are the most essential components. Since, it is hardly available in our country, it is necessary to use a suitable method which subsequently reduces human effort and to increase the productions amidst of the consequences such as leaching of nutrients from soil and water. The main objective of this paper is to use an efficient method of irrigation using the recent trends of our growing technology. It is by using mobile apps or remote control systems which is known as Automatic Irrigation System, which will be of great use to farmers that can be used from home. In this system, the GSM receives message from the user and sends to the microcontroller through which the action is implemented. Thus, this system can be efficiently used for soil and water management through Automation.